ENHANCING STUDENT NUMERACY AND LITERACY WITH GEOGEBRA: A CASE IN NUMERICAL METHODS - Aklimawati, Aklimawati; Lestiana, Yeni; Wulandari, Wulandari; Johar, Rahmah; Khairunnisak, Cut; Isyafani, Erna (KALAMATIKA Jurnal Pendidikan Matematika, 2023)
Rapid advancement in technology has increased the significance of numerical literacy skills. The numerical methods course requires numerical literacy skills. The course enables students to solve a mathematical problem by interpreting the answer using an approximation rather than an actual value. This research used a descriptive quantitative method. The population of this study consisted of 80 university students enrolled in a numerical methods course. The sampling technique used a saturated sample, which involved everyone in the population as the sample. Data were collected from the learning outcomes test and questionnaire responses. The data were analyzed using a quantitative descriptive statistical analysis technique, and the data analysis computations were performed using SPSS Statistics 2. The study showed that the students' Numeracy and Literacy Skills improved when GeoGebra-assisted teaching materials were implemented in the numerical methods.